Optimisation of bile production during normothermic preservation of porcine livers. - Imber, C; St Peter, S; de Cenarruzabeitia, I; Lemonde, H; Rees, M; Butler, A; Clayton, P; Friend, P (2002)
Machine perfusion of livers may provide a mechanism for extended preservation of marginal donor organs before transplantation, as well as a method for viability assessment. It has proved possible in a series of experimental porcine liver perfusions to maintain liver viability for up to 72 h. However, a reduction in bile production with associated histological evidence of cholestasis was seen after 10 h of perfusion, damaging the biliary canaliculi during the preservation period and leaving these organs in an unacceptable condition for transplantation. It was proposed that reduction in bile production was the result of a relentless depletion of available bile salts, gut recirculation not being possible and de-novo synthesis being unable to keep up with loss. This was proved by measuring porcine native bile acids within serial perfusate and bile samples using gas chromatography mass spectrophotometry. It was shown that all three native pig bile acids were decreased to 30% of their original value by 20 h of unsupplemented perfusion. An infusion of taurocholate managed to maintain bile production at physiological levels throughout the 20-h period (8 mL/h +/- 0.75). It was successfully incorporated by the porcine livers into bile. We propose to use this circuit as a novel means of preserving donor livers for transplantation in which the organ is maintained at normal body temperature and perfused with blood. This will reduce ischaemia reperfusion injury and may enable prolonged preservation. The modification described ensures optimal bile production over the entire perfusion period, preventing inspissation and subsequent damage to the canaliculus.